Sorbitol Modulates Resistance to Alternaria alternata by Regulating the Expression of an NLR Resistance Gene in Apple. Issue 7 (5th June 2018) - Meng, Dong; Li, Chunlong; Park, Hee-Jin; González, Jonathan; Wang, Jingying; Dandekar, Abhaya M.; Turgeon, B. Gillian; Cheng, Lailiang
Abstract : Sorbitol acts as a signal regulating the expression of an R protein that interacts with its corresponding effector from Alternaria alternata to confer resistance in apple. Abstract: In plant-microbe interactions, plant sugars produced by photosynthesis are not only a carbon source for pathogens, but may also act as signals that modulate plant defense responses. Here, we report that decreasing sorbitol synthesis in apple ( Malus domestica ) leaves by antisense suppression of ALDOSE-6-PHOSPHATE REDUCTASE ( A6PR ) leads to downregulation of 56 NUCLEOTIDE BINDING/LEUCINE-RICH REPEAT ( NLR ) genes and converts the phenotypic response to Alternaria alternata from resistant to susceptible. We identified a resistance protein encoded by the apple MdNLR16 gene and a small protein encoded by the fungal HRIP1 gene that interact in both a yeast two-hybrid assay and a bimolecular fluorescence complementation assay. Deletion of HRIP1 in A. alternata enables gain of virulence on the wild-type control plant. Overexpression of MdNLR16 in two antisense A6PR lines increases resistance, whereas RNAi suppression of MdNLR16 in the wild-type control decreases resistance against A. alternata . MdWRKY79 transcriptionally regulates MdNLR16 by binding to the promoter of MdNLR16 in response to sorbitol, and exogenous sorbitol feeding partially restores resistance of the antisense A6PR lines to A. alternata . These findings indicate that sorbitol modulates resistance to A. alternata via the MdNLR16 protein that interacts with the fungal effector in a classic gene-for-gene manner in apple.